2005
DOI: 10.4315/0362-028x-68.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Escherichia coli and Genetic Diversity and Antibiotic Resistance Profiling of Salmonella Isolated from Irrigation Water, Packing Shed Equipment, and Fresh Produce in Texas

Abstract: Fresh produce has been repeatedly implicated as a vehicle in the transmission of foodborne gastroenteritis. In an effort to assess the risk factors involved in the contamination of fresh produce with pathogenic bacteria, a total of 1,257 samples were collected from cantaloupe, oranges, and parsley (both in the field and after processing) and from the environment (i.e., irrigation water, soil, equipment, etc.). Samples were collected twice per season from two production farms per commodity and analyzed for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
3
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 38 publications
5
48
3
3
Order By: Relevance
“…Only a limited number of studies have been conducted in the United States to investigate the prevalence of Salmonella and STEC on leafy greens at the farm level. Previous reports have indicated a very low level (Ͻ2%) of Salmonella contamination and largely an absence of STEC on preharvested produce, ranging from 0 to 0.3% (34,(50)(51)(52)(53). The detection of 2.2% of Salmonella-positive leafy greens samples in this study appears to be higher than previously reported.…”
Section: Discussioncontrasting
confidence: 55%
“…Only a limited number of studies have been conducted in the United States to investigate the prevalence of Salmonella and STEC on leafy greens at the farm level. Previous reports have indicated a very low level (Ͻ2%) of Salmonella contamination and largely an absence of STEC on preharvested produce, ranging from 0 to 0.3% (34,(50)(51)(52)(53). The detection of 2.2% of Salmonella-positive leafy greens samples in this study appears to be higher than previously reported.…”
Section: Discussioncontrasting
confidence: 55%
“…Most microbial clusters were detected in produce farms, raising questions as to the possible sources of rodent infection. Food-borne pathogens have been isolated from soil, water, and sediment on produce farm environments (34,48,49); however, no links have been made to rodents in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few publications are available about studies of whether vegetables or the environment where they are produced can act as a carrier or reservoir of antimicrobial resistance (22,23).…”
mentioning
confidence: 99%